Pelayanan Perlindungan Terhadap Perempuan Korban Praktik Pengantin Pesanan (Mail Order Brides) di Indonesia - Irwanzah, Muhammad Rafi; Akturusiano, Binto; Hapsoro Wirandoko, Ignatius (Syntax Corporation, 2025)
This article discusses the experiences of woman who are victims of mail-order bride and the identification of protection services for them as a process of recovery from the violence they have experienced. This research was conducted with a descriptive method. The data were taken from literature studies and women who were victims of the practice of mail-order brides themselves. The result of this study indicate that protection service for women who are victims of mail-order brides are the most essential thing as a forum for healing and recovering from the suffering they experience during and after they become mail-order brides. The experiences of women who are victims of mail-order brides cannot be simply removed from women’s minds, so the role of Non-Government Organization (NGO) such as the Indonesian Migrant Workers’ Union (SBMI) is very helpful for women who are victims of mail-order brides who have returned and are given special services until they feel they can live their lives again. This research can contribute to society, especially knowledge related to the phenomenon of mail-order bride practices and patterns and forms of protection services for women victims of mail-order brides.